PELAYANAN KESEHATAN NEONATAL BERPENGARUH TERHADAP KEMATIAN NEONATAL DI INDONESIA - Sri Sukamti; Pandu Riono (Poltekkes Kemenkes Jakarta III, 2015)
Neonatal mortality rate in Indonesia, namely 19 per 1000 live births, is 55,9% ofthe infantmortality rate.Eventhough there are numbers of Maternal Care Health (MCH) programimplemented, declining neonatal mortality is still slow. Current efforts todecreaseneonatalmortalityare designed through the provision ofneonatalcarevisits. Theyincludes vitaminKinjection, administration ofeye ointment, early detection ofdanger signs, and HB0immunization. This research aims to examinethe effect of neonatal care, particularly neonatalvisit, in relation toreduce neonatal mortality rate in Indonesia (Analisis Data Riskesdas2010). This research employedcross sectional design with total number of sample13.859children those born alive, aged 0-59 months.. Data was analyzed using multiple logisticregression based on the Directed Acyclic Graph (DAG). The result shows that the risk ofneonatal death is higher among neonatal who received less than 3 neonatal visitserviceswithORadj=12.77 (95%CI1,82 - 89,56) than their counter part who did not receive neonatalvisit ORadj=28.32 (95%CI 3,86 - 208,26). Neonateswith novitamin Kat the time of1stneonatal visit has higherrisk ofneonatal death, with p value < 0,001 and OR adj 34,5(95%CI 4,90 - 243,34). This study shows that a high quality of neonatal health servicescould prevent neonatal death in Indonesia.